Efeito da suplementação crônica de curcuma longa l. sobre marcadores de inflamação e dano muscular após uma meia maratona - Faria, Flavia Rasmussen (2016)
Physical exercise increase the antioxidant capaciy of the individual, on the other hand, frequent performance of high intensity or exhaustive physical exercises may increase reactive oxygen species and inflammation, resulting in muscle damage. Curcumin, a yellow-orange component of turmeric, is derived from the turmeric plant (Curcuma Longa L.), and has been studied due to their antioxidant capacity and anti-inflammatory. Objective: To evaluate the effects of Curcuma Longa L. supplementation on markers of inflammation and muscle damage after a half marathon. Methodology: This study consisted of two stages. In the first, it was carried a crossover clinical trial (washout period of seven days). 9 males were supplemented with low (1.5g), medium (3.0g) and high (6.0g) dosages of Curcuma longa L. Blood samples were collected to measure curcumin plasma concentrations and antioxidant capacity. In the second stage, it was performed a double-blind, randomized clinical trial, (34-day). The placebo group (PG) (n = 14) and supplemented (SG) (n = 14) received 1.5 g of cellulose and 1.5 g of Curcuma longa L., respectively. After 30 days, participants performed a half marathon race (21 km). Blood samples were collected to evaluate CK, LDH, ALT, AST, IL-6, IL-10, MCP-1 and myoglobin. Furthermore, it was evaluate the muscle pain and performance. Results Phase 1: The mean age was 26.8 ± 1.3 years and the body mass index (BMI) was 23.31 ± 0,75kg / m2. There were no differences between curcumin concentration and the time and the differents dosages of Curcuma longa L. (p > 0.05). Results Phase 2: The mean age was GS: 34.14 ± 7.18, GP: 36 ± 9.19. Both groups increased the CK, LDH, AST, IL-6, MCP-1, IL-10 and myoglobin concentrations after the run, showing that the protocol was sufficient to generate damage. SG decreased the pain sensation and increased IL-10 concentrations, compared to the PG. Conclusions: Phase 1: Low dose supplementation showed a maximum concentration of plasma curcumin, but no statistical difference when compared to others dosages. Curcumin plasma concentrations did not increase proportional to the dose administered. Step 2: Curcuma Longa L. did not decrease muscle damage after a half-marathon race, however supplementation improved performance, increasead Il-10 concentrations and reduced muscle soreness.